Proposed upgrading kindergarten for Dzuliman at No 20 Tronoh Indah 1, 31250 Tronoh, Perak / Fazlin Awaludin - Awaludin, Fazlin (Faculty of Architecture, Planning and Surveying, 2006)
In order to get a good design al lot of researcher have to been done.From observation itself can ensure self experience to undergo certain project,whetrt it id for exterior or interior Suitable elements are important to produce certain project to get suible concept and images.By doing so,a propiate concept wii be implenmnt.As the results ,a maximum satisfaction for end user A Khalifah Kindergarten is proposed to be an example of the maximized utilization of modem learning technology and traditional Islam. In this development center the goal would be to showcase an ideal learning and Islamic environment. This idealized example could then serve as a model for the creation o f other development centers implementing this idealized program.lt would be the beginning of a research facility to investigate new educational techniques and curricula appropriate to Islam.